Halal issues in pastry and bakery products: the halal gatekeepers of bakery ingredients / Wan Rusni Wan Ismail ... [et al.] - Wan Ismail, Wan Rusni; Ramli, Rafidah Aida; Mohd Zain, Zarifah; Abdullah, Hasniza; Zulkifli, Amirul Hakim; Azahar, Hanisah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
The bakery and pastry industry is one of the fastest growing “cottage” industries in Malaysia. Being a Muslim-majority country, halal is a very important factor in securing the market share. Unlike other ready-to-eat products which ingredients come from raw materials, most ingredients and additives used in bakery and pastry industry are processed food components which raised the uncertainty on their halal status. Using qualitative semi-structured interview, important findings have emerged pointing to somewhat serious issues pertaining to ambiguous ingredients in bakery and pastry application which requires immediate actions. A total of 12 pastry chefs were interviewed about their perception of the halal issue of baking ingredients. Results indicate strong awareness among the practitioners regarding the ambiguous ingredients in pastry and bakery products. However, the uncertainty and doubts of these ambiguous ingredients are often washed away by the trust they put in the ingredient’s suppliers, mentors and halal label on the packaging. Putting trust on other people in finding halal ingredients sounds positive and doubt-free. However, this might also lead us to becoming too complacent with what we use in pastry and bakery products without putting much effort to inspect the halal status of each ingredient we use. Recommendations to enlighten this matter require actions from all responsible parties including the chefs, suppliers, authority (JAKIM) as well as the end-user. This is also in accordance with the Islamic teaching which said that finding the halal food or things are the responsibilities of everyone.